ANALISIS PENGARUH STORE ATMOSPHER, PROMOSI, DAN LEASING TERHADAP KEPUTUSAN PEMBELIAN DI CANDI ELEKTRONIK SURAKARTA - Edi Purnomo; Ida Aryati; Burhanudin Ahmad Yani (JURNAL ILMIAH EDUNOMIKA, 2019)
This study aims to determine the effect of store atmosphere, promotion and leasing on purchasing decisions in Surakarta electronic temple stores. the population in this study were all consumers of Surakarta electronic temple, amounting to 650 people. The number of samples taken in this study were 100 people. The sampling technique in this study was the accidental sampling technique. The data used in this study is a questionnaire using a Likert scale as a measuring instrument. The analysis technique used in this research is linear regression using SPSS version 20 for Windows. Based on the analysis conducted shows that there is an influence of store atmosphere, promotion and leasing on purchasing decisions in the electronic temple shop in Surakarta. Keywords: store atmosphere, promotion, leasing, purchasing decisions